GREATER OMENTUM: MORPHOFUNCTIONAL CHARACTERISTICS AND CLINICAL SIGNIFICANCE IN PEDIATRICS - A.V. Nekrutov; O.V. Karaseva; L.M. Roshal' ("Paediatrician" Publishers LLC, 2007)
The review analyzes the structure organization and pathophysiological age specificities of the greater omentum, which determine its uniqueness and functional diversity in a child's organism. the article discusses protective functions of the organ, its role in the development of post operative complications of children, and the usage in children's reconstructive plastic surgery.Key words: greater omentum, omentitis, of post operative complications, children.